WITCHCRAFT IN THE 20TH AND 21ST CENTURIES IN NIGERIA: AN ANALYSIS - Jayeola-Omoyeni, M.S.; Oyetade, Eunice M.; Omoyeni, J.O. (European Scientific Journal, ESJ, 2015)
This article is aimed at discussing the incidence of witchcraft during the colonial and post-colonial periods in Nigeria, and shows some basic reasons why people were or are indulged in witchcraft. It also discusses the significant impacts of witchcraft in the socio-cultural and technological development of the Nigeria society Witchcraft became a crime as the various communities advanced in technology because of exposure to western education and industrialization. Some communities experienced an intense period of witch-hunting while their neighbours were hardly aware of witchhunting. Many individuals freely admitted to being witches. Such individuals were often non-conformists who felt constrained or alienated, by the plethora of oaths, sanctions and taboos. A witch was believed to be an individual in whom dwelt a distinctive wickedness which harmed people in mysterious secret ways. They were regarded as antisocial and wicked. The witch myth was and is still recognized and affirmed as opposition to moralities. The witch, as an incarnate, always symbolized evil in contrast to the basic goodness of the society. Penalties for witchcraft vary widely in different parts of Africa. In Nigeria, nearly all witchcraft penalties were harsh and rather arbitrary. Witches in pnre-colonial, Nigeria were rarely completely rehabilitated and accepted back into the society. Research findings shows that, things changed in the present day Nigeria where witches having confessed or renounced openly, were ably accepted into their community and freed to take part in community affair as normal persons.